2011
DOI: 10.1111/j.1365-2966.2011.19156.x
|View full text |Cite
|
Sign up to set email alerts
|

Far-infrared luminosity function of local star-forming galaxies in the AKARI Deep Field-South

Abstract: We present a far‐infrared galaxy luminosity function for the local universe. We have obtained 389 spectroscopic redshifts for galaxies observed at 90 μm in the AKARI Deep Field‐South, using the AAOmega fibre spectrograph via optical identifications in the digitized sky survey and 4‐m class optical imaging. For the luminosity function presented in this paper, we have used those galaxies which have redshifts 0 < z < 0.25, have optical magnitudes and are not part of a newly discovered cluster of galaxies (giving … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 71 publications
1
36
0
Order By: Relevance
“…insufficient to detect high-z unlensed galaxies) but conducted a few deep field pointings, including the AKARI deep field South (ADF-S) covering ∼12 deg 2 . The ADF-S hosts several tens of bright 90µm galaxies (the 90µm channel being the most sensitive) yet to be characterized in detail; a number of spectroscopic redshifts for the galaxies have been compiled in Sedgwick et al (2011). The AKARI observatory also hosted the InfraRed Camera (IRC; Onaka et al, 2007) operated at shorter wavelengths, from 2.4-24µm, yet was not focused on deep-field extragalactic work as Spitzer IRAC and MIPS fulfilled that role.…”
Section: Far-infrared Surveyor [Fis] 2006-2011mentioning
confidence: 99%
“…insufficient to detect high-z unlensed galaxies) but conducted a few deep field pointings, including the AKARI deep field South (ADF-S) covering ∼12 deg 2 . The ADF-S hosts several tens of bright 90µm galaxies (the 90µm channel being the most sensitive) yet to be characterized in detail; a number of spectroscopic redshifts for the galaxies have been compiled in Sedgwick et al (2011). The AKARI observatory also hosted the InfraRed Camera (IRC; Onaka et al, 2007) operated at shorter wavelengths, from 2.4-24µm, yet was not focused on deep-field extragalactic work as Spitzer IRAC and MIPS fulfilled that role.…”
Section: Far-infrared Surveyor [Fis] 2006-2011mentioning
confidence: 99%
“…The central part of the ADF-S (inside KMTNet-R2 region in Figure 1) Oliver et al (2012) was also observed by AKARI /IRC, APEX/LABOCA, ASTE/AzTEC and ATCA at 2-24µm, 870µm, 1.1mm and 20cm, respectively. Optical spectroscopic information is available only in this region (Sedgwick et al 2011). Other follow-up multi-wavelength surveys for the central region of the ADF-S are described in Clements (2012).…”
Section: The Adf-s and Kmtnet Surveymentioning
confidence: 99%
“…errors: it can also be real, since our sample of z spec is strongly biased towards low redshifts by the selection made by the observers (Sedgwick et al, 2011). The median value of z CIGALE is closer to those of z spec and equal to 0.06.…”
Section: Resultsmentioning
confidence: 98%
“…Some of them were collected from public databases (NED and SIMBAD). Additionally, we use redshift measurements of Sedgwick et al (2011).…”
Section: Redshift Informationmentioning
confidence: 99%